Multinationals, Clusters and Innovation Does Public Policy Matter? - Tavares, A.; Teixeira, A.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2006)
Countries adopt policies that attract foreign multinationals, stimulate industrial clustering and foster innovation. This book links these topical issues, examining activities of multinational enterprises alongside the efficiency, appropriateness and sufficiency of such policies. With new empirical evidence, it makes practical proposals throughout.
Keywords: International business enterprises; International economics; Public policy; International Business; International Economics; Public Policy